2019
DOI: 10.1186/s12872-019-1131-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cardiovascular disease and its associated risk factors in at-risk men and women in the United Arab Emirates: a 9-year retrospective cohort study

Abstract: Background Cardiovascular disease (CVD) is the leading cause of mortality worldwide; however, the epidemiology of CVD among nationals from the United Arab Emirates (UAE) remains unknown. This study aimed to estimate the 9-year incidence rate of CVD and determine the risk factors associated with CVD among UAE nationals at high cardiovascular risk. In addition, we investigated whether sex was an important modifier of the risk factors associated with incident CVD in this population. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
6
46
1
Order By: Relevance
“…Similarly, diabetic patients with systolic HTN comorbid had more than four-fold higher risk of developing CVD than those who had no systolic HTN which agrees with the ndings from other longitudinal studies (14,18,44). Even though the recent guideline by American College of Cardiology and American Heart Association showed importance of detection, evaluation and management of high blood pressure in reducing the risk of CVD (45), a signi cant number of patients fail to achieve blood pressure targets in developing countries (46).…”
Section: Predictors Of Cvd Among Diabetic Patientssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, diabetic patients with systolic HTN comorbid had more than four-fold higher risk of developing CVD than those who had no systolic HTN which agrees with the ndings from other longitudinal studies (14,18,44). Even though the recent guideline by American College of Cardiology and American Heart Association showed importance of detection, evaluation and management of high blood pressure in reducing the risk of CVD (45), a signi cant number of patients fail to achieve blood pressure targets in developing countries (46).…”
Section: Predictors Of Cvd Among Diabetic Patientssupporting
confidence: 89%
“…Several epidemiological researchers around the world identi ed older age and longer duration of DM (14), high density lipoprotein cholesterol (HDL-C) level (15), smoking and heavy alcohol consumption (16), hypertension (HTN) (17,18), poor glycemic control (high glycosylated hemoglobin (HbA1c) (18) and triglyceride (TG) (19) to be independent predictors for incident CVD. In response to the recent rise of CVDs in developing countries, World health organization (WHO) has identi ed very cost-effective interventions that are applicable even in low-resource settings for prevention and control of CVDs (20).…”
Section: Introductionmentioning
confidence: 99%
“…For adults ≤39 years of age, there are sparse data relating to the utility and performance of the 2013 PCE risk prediction model. In the UAE national population, age has been shown to be an independent predictor of incident CVD, 25 with several studies in the region having reported a high incidence of atherosclerotic CVD in younger age groups. 26–28 A study conducted in six Middle Eastern countries, including the UAE, found that 50% of patients diagnosed with an acute coronary syndrome were aged <55 years, a decade younger than those being diagnosed in North America and Europe.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiovascular risk prediction tools, such as the FRS model, have been widely recommended by international and local guidelines to better target primary preventive treatments, particularly lipid-lowering therapy, in susceptible individuals [15,21]. However, the FRS model does not include emerging risk factors, such as renal failure, which is associated with increased cardiovascular risk among UAE nationals [5]. Therefore, developing novel risk prediction models based on local data would be more appropriate in populations with varying disease patterns and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the Middle East, CHD is by far the most serious public health concern [2,3]. Premature deaths associated with CHD have tripled over the past decade [4] and in a recent United Arab Emirates (UAE) study, the cumulative incidence of acute CHD events among men with one or more vascular risk factors was noted to be 8.9% over nine years [5]. While the crude incidence of acute CHD over ten years was 4.7% among European men in the general population [6].…”
Section: Introductionmentioning
confidence: 99%